Hubungan Perilaku Sedentary lifestyle dengan Tingkat Risiko Kejadian Diabetes Melitus pada Remaja - Ressa Julliyana; Popi Sopiah; Rafika Rosyda (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Diabetes mellitus (DM) is a metabolic disease that is generally suffered by adults, but also suffered by many adolescents. Factors causing the high risk of adolescents suffering from DM are a lack of preventive measures and high sedentary behavior, causing a buildup of sugar in the body due to low muscle work. The purpose of this study was to determine the relationship between a sedentary lifestyle and the risk level of DM in adolescents. This study is a correlational quantitative study with a cross-sectional approach. The sample size of this study was 127 respondents from 674 total population selected using a proportionate stratified random sampling technique. The analysis method used was Spearman's rho correlation test. This study uses two research instruments, which are ASAQ and FINDRISC instruments. The results of the study obtained the highest data in high sedentary behavior (74%) and respondents at low risk of DM (72%) with the results of the correlation test p-value=0.031 (<0.05) and r=0.191. This shows that there is a relationship between a sedentary lifestyle and the level of risk of DM in adolescents, with a positive direction. Therefore, adolescents are advised to avoid sedentary behavior to reduce the risk of suffering from DM.